The Relationship between Life Skills Training with Social Adjustment and the Self-esteem of Mentally Retarded Boy and Girls Students in the Primary Schools of the Jam City - ashidi, Fateme R; Salari, Ahmad (IJRDO- Journal of Educational Research, 2017)
Extensive studies have been done on the effectiveness of life skills training on students’ behavior. However, little studies have been done about the effectiveness of life skills training on the behavior of students with disabilities. Given that the need of these groups of students to these skills is more than others, planning and implementation is particularly important in this regard. The aim of this study was to examine the relationship between life skills training with social adjustment and the self-esteem of mentally retarded boy and girl students in Jam. The plan of the study was a quasi-experimental study with pre-test and post-test with control and experimental groups. The population of the study was 60 mentally retarded boy and girls students in the primary school of Jam which were selected by census method and were divided into two experimental and control groups, each group has 30 students. The experimental group were taught life skills in twelve session, each session lasts for one-hour. Social adjustment and selfesteem of both groups were estimated before and after training using social adjustment Bell Standard Questionnaire (1961) and Self-esteem criteria (1964). To analyze collected data, Pearson Correlation test was used. The results of this study showed that in compared to control group, experimental groups had better performance in the test. Life skill training significantly increased social adjustment and self-esteem.